Advanced Adobe Acrobat XI training - Hoffman, Michael (InfiniteSkills, 2013)
"In this Advanced Acrobat XI training course, expert Michael Hoffman shows you how to take your documents to the next level in Adobe Acrobat. This software is a collaborative tool that provides a seamless and automated environment for almost any document management need you may have. This advanced course is designed for users that already have a basic working knowledge of Acrobat XI. Once you have completed this Advanced / Security Acrobat training course, you will have a clear understanding of how to more effectively use the features that Acrobat has to offer your document management process. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.